The character and the lives of youths today - Borneo Post, (KK) (Borneo Post (KK), 2012)
SHAH ALAM : There is a general consensus in our society that the younger generation today, regardless of their racial and religious background, no longer believe in the ideal way of life that our ancestors lived.